The Role of Radiotherapy in Early-stage Primary Diffuse Large B-Cell Lymphoma of the Waldeyer Ring: A Retrospective Cohort Study. (August 2018) - Lee, Shing Fung; Ng, Ting Ying; Wong, Frank Chi Sing; Tung, Stewart Yuk
Abstract : Objectives: The role of radiotherapy (RT) in improving survival of patients with diffuse large B-cell lymphoma (DLBCL) of the Waldeyer ring (WR) remains controversial. Therefore, this retrospective cohort study aimed to determine the role of RT in the treatment of DLBCL of the WR as well as the effects of associated covariates. Materials and Methods: Patients (n=35) with stage I to II DLBCL of the WR who underwent treatment at our center between 1994 and 2010 were retrospectively investigated. All patients had histologic diagnosis and staging workup completed. Overall survival (OS), event-free survival (EFS), and disease-free survival (DFS) were analyzed. Variables with a P -value of <0.1 were subjected to multivariate Cox proportional hazards model analyses. Results: The median OS was 8.1 years. The 5-year OS, DFS, and EFS rates were 59.4%, 53.8%, and 70.7%, respectively; the corresponding 10-year rates were 34.9%, 29.5%, and 51.0%, respectively. The 5-year OS rate was significantly higher in the RT group than in the non-RT group (65.4% vs. 36.4%, respectively; P =0.008). On multivariate analysis, RT was associated with improved OS (hazard ratio=0.15; 95% confidence interval [CI], 0.04-0.50; P =0.002) and EFS (hazard ratio=0.29; 95% CI, 0.095-0.86; P =0.026). An Eastern Cooperative Oncology Group performance status >1 and age above 60 years were also found to negatively influence OS and EFS. Conclusions: RT was associated with improved OS and EFS in stage I to II DLBCL of the WR. Future prospective studies are required to confirm these findings. Abstract : Supplemental Digital Content is available in the text.